¿Es constitucional que un afiliado al sistema privado de pensiones pueda acceder hasta el 95,5% de los fondos de su cuenta individual de capitalización? - Calle Cabrera, Pía Stephania (2017)
Through this article, the Investigation Commission of the Commercial Law Team makes an approximation to the Private Pension System in Peru, the main changes introduced by Law 30425 and, finally, the constitutionality of the provision that allows the member can access up to 95.5% of its funds.